Plasma taurine estimation in dilated cardiomyopathy of labrador retrievers - K. Jeyaraja; G. Sarath Chandra; Hamsa Yamini; P.S. Thirunavukkarasu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The objective of this study was to quantify the concentrations of taurine in the plasma of Labrador retrievers with clinical disease of Dilated Cardiomyopathy (DCM) and to compare with the healthy Labrador retrievers. The study was conducted in thirty clinical cases of Dilated cardiomyopathy (DCM) in Labrador Retrievers and in thirty healthy Labradors. The plasma taurine estimation by HPLC showed a highly significant decrease in taurine levels (18.712 ± 3.53 nmol/mL) in dogs with Dilated cardiomyopathy compared to healthy dogs (51.022 ± 5.55 nmol/mL). Therefore, it was concluded that there was a significant role of plasma taurine in the pathogenesis of Dilated cardiomopathy in Labrador Retrievers . This pilot study justifies the supplementation of taurine in DCM of Labradors and also it opened up a new area for extensive research at a larger scale involving multi centres. In addition a commercially viable method for estimation of taurine was developed.